ANALISIS FAKTOR KESIAPSIAGAAN MASYARAKAT DALAM MENGHADAPI BENCANA TANAH LONGSOR DI DESA CANDIREJO SEMIN GUNUNGKIDUL - Cahyo Pramono Cahyo; Ahmad Muzaki; Ervina Kurniawati (STIKES Pemkab Purworejo, 2024)
The Special Region of Yogyakarta, especially in Gunungkidul Regency in Candirejo Village, Semin District, there is the potential for a landslide disaster in November 2022 which causes 2 casualties and property damage. So it is important for residents to have preparedness in facing disasters in order to avoid casualties. The purpose of the study was to analyze community preparedness factors in facing landslide disasters. This study used a quantitative descriptive research design with a cross sectional approach. The sampling technique uses Purposive sampling. The sample used was 86 respondents. Data collection tools using questionnaires. Statistical tests using Kendall's Tau test. The results of the study were obtained, the age of respondents 45-60 years, namely 54 respondents with sufficient preparedness 35 respondents (64.8%), education respondents with basic education 46 respondents with sufficient preparedness 31 respondents (67.4%), respondents' experience never 63 respondents with sufficient preparedness 34 respondents (54.0%). The results of Kendall's Tau test show that there is a relationship between age and education with community preparedness in facing landslides (p = <0.05). There is no relationship between the experience of experiencing a disaster and community preparedness in facing landslides (p = >0.05). Age and education are related to community preparedness in facing landslides in Candirejo Village, Semin, Gunungkidul